Human Occupation of the North American Colorado Plateau ∼37,000 Years Ago - Rowe, Timothy B.; Stafford, Thomas W.; Fisher, Daniel C.; Enghild, Jan J.; Quigg, J. Michael; Ketcham, Richard A.; Sagebiel, J. Chris; Hanna, Romy; Colbert, Matthew W. (Frontiers in Ecology and Evolution, 2022)
Calibrating human population dispersals across Earth’s surface is fundamental to assessing rates and timing of anthropogenic impacts and distinguishing ecological phenomena influenced by humans from those that were not. Here, we describe the Hartley mammoth locality, which dates to 38,900–36,250 cal BP by AMS 14C analysis of hydroxyproline from bone collagen. We accept the standard view that elaborate stone technology of the Eurasian Upper Paleolithic was introduced into the Americas by arrival of the Native American clade ∼16,000 cal BP. It follows that if older cultural sites exist in the Americas, they might only be diagnosed using nuanced taphonomic approaches. We employed computed tomography (CT and μCT) and other state-of-the-art methods that had not previously been applied to investigating ancient American sites. This revealed multiple lines of taphonomic evidence suggesting that two mammoths were butchered using expedient lithic and bone technology, along with evidence diagnostic of controlled (domestic) fire. That this may be an ancient cultural site is corroborated by independent genetic evidence of two founding populations for humans in the Americas, which has already raised the possibility of a dispersal into the Americas by people of East Asian ancestry that preceded the Native American clade by millennia. The Hartley mammoth locality thus provides a new deep point of chronologic reference for occupation of the Americas and the attainment by humans of a near-global distribution.